PERAN GURU DALAM PEMBENTUKAN KARAKTER PEDULI SISWA TERHADAP LINGKUNGAN MELALUI KEGIATAN PEMBIASAAN MEMBUANG SAMPAH - Vinna Ainun Zachroh; Husna Farhana (Program Studi Pendidikan Guru Sekolah Dasar Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2024)
Schools that prioritize environmental sustainability despite fostering an environmental culture continue to encounter challenges, such as students misplacing trash and the presence of plastic cup waste within the campus environment. As it relates to the practice of littering at SDN Mustika Jaya III, the purpose of this study is to determine the extent to which instructors influence students' environmental consciousness. Descriptive qualitative methodology was employed to depict the actual conditions, and the resulting data consists of sentences and images. This research utilizes class IIIA instructors, class VC instructors, and class VC students as its data sources. As a result of this research, teachers serve as facilitators and motivators, in addition to acting as mentors and educators who establish habits. Nonetheless, scholars continue to observe subpar performance among educators, as evidenced by the inadequate dissemination of information regarding schools that embrace an environmental culture; as a result, pupils continue to lack comprehension regarding the nature of such institutions. As an indication of students' lack of awareness and concern for the surrounding environment, particularly in schools, there are still students who improperly dispose of trash, causing environmental damage, and there are insufficient learning facilities at schools.